C FOR CONFLICT: DISPOSITIVE CENTERS AND THE DISCURSIVE CONSTRUCTION OF JUVENILE DELINQUENCY - Nathaniel G. Gido; Wilzen D. Bermoy; Maricar G. Cañedo (Galaxy International Interdisciplinary Research Journal, 2022)
This paper is using critical analysis to examine how the discursive idea of "juvenile delinquency" has formed and evolved among Cebuanos—both children and adults. The study is an overall expansion of the qualitative methodology. The critical discourse analysis (CDA) methods guide the level of in-depth study regarding texts and contents. The end result is a multifunctional and multifaceted structure: a prison-orphanage-school-cloister-in-one. For mortification, digital surveillance is used, and the jail security apparatus, as well as the jail personnel themselves, serve as a superimposed substitute for parenting and scapegoating. No wonder, based on the statistical data we have found regarding the juvenile delinquency rate and the facts about what usually happens when CICL leave the centers and then rejoin the free communities, self-defense alibi and self-victimization cases are rampant among the children abused to do the evil deeds of adults. The divergence programs have evolved into a program to amplify divergence. To feel "clean" and rehabilitated, all they have to do is eat, pray, and love their country and religion indefinitely. Furthermore, Children in Conflict with the Law are regarded as grounded miniature adults.